DEMOGRAPHIC ANALYSIS OF SOUTH MUNTENIA REGION - Cătălina Nicoleta COMAN; Valentina TUDOR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper aims to carry out a study research on the structure of the population in the South-Muntenia development region through which analyzed and interpreted statistical data are combined with theoretical aspects and lead to a detailed analysis of the regional information on the structure of the population in the South Muntenia region. The population of South-Muntenia development region, which includes the counties Argeş, Călăraşi, Dâmboviţa, Giurgiu, Ialomiţa, Prahova and Teleorman, equals 2.984.992 persons in 2017 and represents over 15% of the total population of Romania.